Investigating the fracture and deformation behaviour of pre-strained Grade 91 steel under small punch loading (Fracture and Structural Integrity, 2026)
Various failure modes induce localized internal damage and stress concentration sites in power plant components, causing additional plasticity that degrades material strength. Effect on such localized plasticity on components durability cannot be accurately evaluated using conventional mechanical tests which require large specimens. This study investigates the effect of plasticity on the deformation and fracture behaviour of Grade 91 steel using small punch testing (SPT). Initially, plasticity was introduced by mechanically pre-straining the material to 4%, 8%, and 12% strain levels. The deformation and fracture behaviour of the pre-strained specimens were then assessed under small punch loading. Pre-straining significantly influences the load–displacement response, producing a clear increase in yield load, while the maximum load and corresponding displacement decrease progressively with increasing pre-strain. Moreover, fracture occurs at lower displacement values at higher pre-strain levels. At the macroscopic scale, fracture exhibits mixed ductile–brittle characteristics with limited necking. Microscopic observations further confirm a pronounced reduction in ductility with increasing pre-strain. Furthermore, numerical simulations accurately predict the onset and location of fracture as well as the stress distribution in SPT samples, validating the modelling approach for pre-strained materials. Overall, this study supports improved assessment of structural integrity in components subjected to long-term plastic deformation.
Keywords: Deformation; Fracture; Grade 91 Steel; Pre-straining; Small Punch